Impacts of coral bleaching on reef fish abundance, biomass and assemblage structure at remote Aldabra Atoll, Seychelles: insights from two survey methods - Koester, Anna; Gordó−Vilaseca, Cesc; Bunbury, Nancy; Ferse, Sebastian C. A.; Ford, Amanda; Haupt, Philip; A’Bear, Luke; Bielsa, Maria; Burt, April Jasmine; Letori, Jake; Mederic, Emma; Nancy, Ella; et al. (Frontiers in Marine Science, 2023)
Introduction Coral bleaching immediately impacts the reef benthos, but effects on fish communities are less well understood because they are often delayed and confounded by anthropogenic interactions. Methods We assessed changes in fish abundance, biomass and community composition before and after the 2015/16 coral bleaching event at Aldabra Atoll, Seychelles, where local human impacts are minimal, but reefs suffered 50% bleaching-induced coral mortality. We monitored 12 shallow (2–5 m water depth) and nine deep (15 m water depth) permanent survey sites using two survey methods: indicator surveys recording 84 taxa over six years (pre-: 2014; post-bleaching: 2016–2019, 2021), sizing fish based on six size-class categories, and extended fish surveys recording 198 taxa over two years (pre-: 2015; post-bleaching: 2020) with size estimates to the nearest cm (excluding fish < 8 cm). Results During indicator surveys, mean fish abundance did not change on deep reefs. However, abundance increased by 77% on shallow reefs between 2014 and 2016, which was mainly driven by increases in herbivores and omnivores, likely as a response to elevated turf algae cover following coral mortality. Overall (and functional group-specific) indicator fish biomass did not differ between 2014 and 2016 and remained at or above pre-bleaching levels throughout 2016–2021. In contrast, extended fish surveys in 2015 and 2020 showed a 55–60% reduction in overall abundance on shallow and deep reefs, and a 69% reduction in biomass on shallow reefs, with decreases in biomass occurring in all functional groups. Biomass on deep reefs did not differ between 2015 and 2020. Multivariate analysis of both data sets revealed immediate and long-lasting differences between pre- and post-bleaching fish community compositions, driven largely by herbivorous, omnivorous and piscivorous taxa. Discussion Results from the indicator surveys suggest that the bleaching event had limited impact on fish abundance and biomass, while the extended surveys recorded changes in abundance and biomass which would otherwise have gone undetected. Our findings improve understanding of the shift a broad community of fish undergoes following a mass coral bleaching event and highlights the value of survey methods that include the full suite of species to detect ecological responses to environmental drivers.